Ionospheric Response along Meridian for the Certain Storm Using TEC and foF2 - Olga Maltseva; Artem Kharakhashyan; Tatyana Nikitenko (Universe, 2021)
For a long time, the equivalent ionospheric slab thickness τ has remained in the shadow of ionospheric main parameters: the maximum density, NmF2 (or the critical frequency, foF2), and the total electron content. Empirical global models have been developed for these two parameters. Recently, several global models of τ have appeared concurrently. This paper compares τ of the Neustrelitz equivalent slab thickness model (NSTM), with τ(IRI-Plas) of the IRI-Plas model, and τ(Appr) of the approximation model, constructed along the 30° E meridian using data from several ionosondes. The choice of the model of the best conformity with observational data was made, which was used to study the effects of space weather during several magnetic storms in March 2012. The effects included: (1) a transition from negative disturbances at high latitudes to positive ones at low latitudes, (2) the super-fountain effect, which had been revealed and explained in previous papers, (3) a deepening of the main ionospheric trough. The efficiency of using τ(Appr) and τ(IRI-Plas) models for studying the effects of space weather has been confirmed. The advantage of the τ(Appr) model is its closeness to real data. The advantage of the τ(IRI-Plas) model is the ability to determine foF2 without ionosondes. The efficiency of the NSTM model is insufficient for a role of a global τ model due to the accuracy decreasing with the increasing latitude.